Resiliency and healing in expressions of Afrocentric education and social work in Canada - Ouedraogo, Valerie; Ikeorji, Chika (My University, 2025)
As a team of educators and researchers in Social Work we are exploring through a qualitative study, the existing expressions in the form of ways of thinking and doing one's work as educator, community worker, and government worker that aligns with Afrocentric Education in Canada. Our poster presentation draws from this research project that is in alignment with the United Nations (UN) International Decade for People of African Descent (IDPAD), and the recommendation 94 (e) in the report of the Working Group of Experts on IDPAD who visited Canada from October 17 to 21, 2016 articulating the need for Afrocentric education in Canada. The study covers three provinces in Canada: Alberta, Nova Scotia, and Ontario. Using profiling, we selected portions of the semi-structured interviews that resonate with Resiliency and Healing as a need for Act Now proposed by the conference call. We will focus on sharing the results of our analysis as a poster guided by our interconnectedness to the data on how participants express Afrocentric Education in Canada using Resiliency and Healing. Our poster is about the meanings/stories that they do tie to these words in responding to the 94e UN IDPAD recommendation to strengthen Afrocentric Education in Canada.
Presented on March 19-21, 2025, at ACT Now! 3rd National Conference on Black Mental Health & Wellness hosted by TAIBU Community Health Centre at the Westin in Edmonton, Alberta.
Keywords: Afrocentric education; Afrocentricity; social work